Preparation method of a crystal face anchoring type self-repairing moisture-proof reflection packaging structure of a lanthanum bromide scintillation crystal

CN122879838APending Publication Date: 2026-10-09NORTHWESTERN POLYTECHNICAL UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611075169.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0014]本发明的目的在于解决现有溴化镧晶体封装方案存在的工艺复杂,难以小型化、无自修复能力等技术问题,而提供了一种溴化镧闪烁晶体的晶面锚固型自修复阻湿反射封装结构制备方法,同时也适用于其他强吸湿卤化物闪烁晶体的封装

Benefits of technology

[0047]1、显著降低封装工艺对惰性气氛手套箱的依赖,适合规模化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879838A_ABST
    Figure CN122879838A_ABST
Patent Text Reader

Abstract

The application provides a crystal face anchoring type self-repairing moisture-proof reflective packaging structure of a lanthanum bromide scintillation crystal, and solves the technical problems of complex process, difficulty in miniaturization and lack of self-repairing capability of existing lanthanum bromide crystal packaging schemes.The crystal face anchoring type self-repairing moisture-proof reflective packaging structure of the lanthanum bromide scintillation crystal comprises a composite layer matched with a lanthanum bromide scintillation crystal body and an optical window; the composite layer is used for packaging non-light-out surfaces of the lanthanum bromide scintillation crystal body, and comprises, from inside to outside, an externally added nano anchoring moisture-proof interface layer, a fluorine-containing polymer reflective layer and a self-repairing moisture-proof protective layer; the optical window is used for packaging light-out surfaces of the lanthanum bromide scintillation crystal body and an end surface of the composite layer flush with the light-out surfaces, and is adhered to the light-out surfaces and the end surface of the composite layer through low-moisture ultraviolet light curing glue, so as to form a high-transmittance, low-stress and moisture-proof sealing interface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of scintillation crystal packaging technology, specifically relating to a method for preparing a crystal plane anchoring type self-healing moisture-resistant and reflective packaging structure for lanthanum bromide scintillation crystals. Background Technology

[0002] Lanthanum bromide (LaBr3) crystal is a high-performance inorganic scintillator with outstanding advantages such as high light yield, good energy resolution, and short decay time, showing broad application prospects in fields such as nuclear radiation detection, high-energy physics, and medical imaging. However, lanthanum bromide crystal is extremely hygroscopic, readily reacting with water vapor in the air and deliquescing, leading to a sharp decline in its scintillator performance or even complete failure. Therefore, effective encapsulation and protection of lanthanum bromide crystal is a key technological step towards its practical application.

[0003] Currently, several technical solutions for encapsulating lanthanum bromide crystals have been disclosed, but each has its own limitations.

[0004] Chinese patent CN107390251B discloses a waterless encapsulation scheme that uses a metal casing, end caps, and window plates to enclose a scintillation crystal inside the casing using vacuum cold pressing technology. This scheme achieves good moisture isolation, but the metal casing results in an excessively large and heavy package, and the vacuum cold pressing process requires sophisticated equipment, making mass production difficult.

[0005] Chinese patent application CN110592669A discloses a high-temperature resistant packaging scheme, which uses a top cover, a sleeve, and a sealing cap to form a metal shell. The crystal is wrapped with PTFE tape, and the seal is achieved through threads and sealant. This scheme is suitable for high-temperature environments such as oil well logging. However, the PTFE reflective layer is only physically wrapped on the crystal surface and lacks chemical bonding with the crystal. During long-term service, it is prone to peeling due to thermal stress. At the same time, the tightness of the wrapping directly affects the light output performance of the crystal, and process consistency is difficult to strictly control.

[0006] Chinese patent application CN109459782B discloses a chemical silver plating encapsulation method, which involves preparing a silver-plated reflective layer on the surface of a scintillation crystal followed by anhydrous encapsulation. This method ensures close contact between the reflective layer and the crystal, which helps prevent detachment. However, the reflectivity of the chemically plated silver layer in the lanthanum bromide emission band (370-390 nm) is lower than that of fluoropolymer materials, and the aqueous solution environment during the silver plating process poses a risk of corrosion to the highly hygroscopic crystal surface. Furthermore, this method does not address the core issue of preventing crystal desiccation.

[0007] Chinese patent application CN215728863U discloses a multilayer composite encapsulation film scheme. This encapsulation film, from the outside in, includes a protective layer, an outer adhesive layer, a waterproof layer, an inner adhesive layer, and a reflective layer. The protective layer is a PET layer, the waterproof layer is an aluminum foil layer, the inner adhesive layer is a high-temperature resistant, anhydrous, oil-based adhesive, and the reflective layer is sealed and bonded to a scintillation crystal. The multilayer structure collectively blocks moisture. This scheme achieves good moisture-proof performance through the multilayer composite film; however, its reflective layer is located in the innermost layer and only contacts the crystal, lacking a structural design to enhance interfacial adhesion. Furthermore, the reflective layer and the moisture-proof layer are connected by an adhesive, which poses a risk of aging and delamination during long-term use.

[0008] A comprehensive and in-depth analysis of the existing technologies reveals that lanthanum bromide crystal packaging still suffers from the following deep-seated technical defects:

[0009] 1. The packaging process is highly dependent on the inert atmosphere, resulting in low efficiency in large-scale production. Most existing packaging processes require the entire process, from crystal cutting, polishing, reflective layer encapsulation to shell sealing, to be completed in an inert gas glove box. This not only requires the glove box to have a sufficiently large operating space and strict water and oxygen control (usually H2O and O2 concentrations are both below 1 ppm), but also allows only a small number of crystals to be processed per batch. The operation steps are cumbersome and time-consuming, making it difficult to achieve continuous and large-scale production.

[0010] 2. Traditional shell-type packaging is too bulky and heavy, making it difficult to achieve miniaturization. Traditional shell-type mechanical packaging requires a multi-component assembly structure, including a metal shell, end caps, and optical windows. To ensure airtightness, the shell wall thickness and sealing rings are often increased, causing the overall size of the detector to expand several times compared to the crystal itself and the weight to increase significantly. This makes it difficult to meet the urgent needs for miniaturization and lightweighting in portable detection devices and space-constrained scenarios.

[0011] 3. Insufficient bonding strength between the reflective layer and the crystal interface. In existing lanthanum bromide scintillation crystal encapsulation technology, the reflective layer (such as a polytetrafluoroethylene (PTFE) micropowder layer or PTFE film) is usually directly coated or simply bonded to the crystal surface, resulting in very limited interfacial bonding strength between the reflective layer and the crystal. During long-term service, it is prone to peeling due to thermal stress or mechanical vibration, directly affecting light output performance.

[0012] 4. Lack of self-healing capability after encapsulation layer damage. Existing moisture-proof encapsulation mainly relies on physical barriers such as metal shells, sealants, or polymer coatings to achieve moisture isolation, which is a passive protection mechanism. Once the encapsulation layer develops microcracks due to mechanical scratches, temperature cycling stress, or aging, moisture will rapidly penetrate to the crystal surface along the crack channels, causing lanthanum bromide to deliquesce and deteriorate. Moreover, the cracks cannot heal themselves, resulting in irreversible degradation of device performance, requiring re-encapsulation. Although microcapsule self-healing technology has been applied in the coating field, its introduction into the moisture-proof encapsulation of highly hygroscopic scintillation crystals requires simultaneously meeting stringent requirements such as low moisture permeability, compatibility between the repair agent and the substrate, and mild curing conditions that do not damage the crystal. Existing technologies have not yet successfully combined these requirements.

[0013] Therefore, there is an urgent need to propose a novel lanthanum bromide crystal packaging structure that combines miniaturization, high reflectivity, and damage self-healing capabilities, while also simplifying the process and reducing dependence on inert atmosphere. Summary of the Invention

[0014] The purpose of this invention is to solve the technical problems of existing lanthanum bromide crystal packaging solutions, such as complex processes, difficulty in miniaturization, and lack of self-healing capability. Instead, it provides a method for preparing a crystal plane anchored self-healing moisture-resistant and reflective packaging structure for lanthanum bromide scintillation crystals, which is also applicable to the packaging of other strongly hygroscopic halide scintillation crystals.

[0015] To achieve the above objectives, the technical solution provided by this invention is:

[0016] A crystal plane anchoring type self-healing moisture-proof and reflective encapsulation structure for a lanthanum bromide scintillation crystal is characterized by including a composite layer and an optical window that cooperate in encapsulating the lanthanum bromide scintillation crystal body.

[0017] The composite layer is used to encapsulate the non-light-emitting surface of the lanthanum bromide scintillation crystal body, and from the inside out, it includes an externally added nano-anchored moisture-proof interface layer, a fluoropolymer reflective layer, and a self-healing moisture-proof protective layer.

[0018] The optical window is used to encapsulate the light-emitting surface of the lanthanum bromide scintillation crystal body and the end face of the composite layer flush with the light-emitting surface. It is bonded to the light-emitting surface and the end face of the composite layer by a low moisture-permeable ultraviolet curing adhesive to form a sealing interface with high light transmittance, low stress, and moisture resistance.

[0019] Furthermore, the externally added nano-anchored moisture-blocking interface layer has a continuous and dense moisture-blocking phase on the side near the lanthanum bromide scintillation crystal body to prevent water vapor from diffusing to the crystal surface, and a mechanically anchored interface with an uneven morphology on the side away from the lanthanum bromide scintillation crystal body to physically embed the fluoropolymer reflective layer within the interface, thereby preventing the peeling of the fluoropolymer reflective layer and improving the adhesion of the subsequent fluoropolymer reflective layer; the thickness of the externally added nano-anchored moisture-blocking interface layer is 8-10 μm, wherein the surface roughness Ra of the mechanically anchored interface is 1.3-2.3 μm, preferably in the range of 1.5-2.2 μm, and preferably 1.8±0.5 μm;

[0020] The externally added nano-anchored moisture-proof interface layer is prepared from a low water vapor permeability matrix, inorganic nanoparticles, dispersant I, and curing agent I;

[0021] The low water vapor permeability matrix is ​​one or more of fluorosilicone resin, fluorocarbon resin, modified organosilicon resin, or parylene.

[0022] The inorganic nanoparticles are one or more of hydrophobically modified nano-silica, nano-alumina, or nano-titanium dioxide, with an average particle size of 10-100 nm.

[0023] The dispersant I is one or more of the following: polymeric dispersant, siloxane dispersant, wetting dispersant, and phosphate ester dispersant;

[0024] The curing agent I is one or more of the following: isocyanate curing agents, amine curing agents (such as modified polyetheramine, triethylenetetramine), acid anhydride curing agents, and latent curing agents (such as 2-methylimidazole, phthalic anhydride).

[0025] Furthermore, the fluoropolymer reflective layer is a polytetrafluoroethylene micro powder layer, expanded polytetrafluoroethylene film, polytetrafluoroethylene composite coating, fluorinated ethylene propylene copolymer coating, or polyvinylidene fluoride coating, which forms an interlocking structure with the mechanical anchoring interface, has a thickness of 80-120 μm, and has a reflectivity greater than 90% in the lanthanum bromide emission band of 370-390 nm.

[0026] Furthermore, the thickness of the self-healing moisture-proof protective layer is 5-500 μm (preferably 90-110 μm), and the self-healing efficiency is 76%-93%. It is prepared from a moisture-proof polymer matrix, microcapsules, dispersant II, and curing agent II.

[0027] The moisture-barrier polymer matrix is ​​epoxy resin, polyurethane resin, silicone resin, fluorocarbon resin or acrylic resin;

[0028] The dispersant II is polyethylene glycol, polyvinyl alcohol, sodium polyacrylate, phosphate ester dispersant, or polymer block copolymer dispersant;

[0029] The curing agent II is a latent curing agent (such as 2-methylimidazole, phthalic anhydride), an amine curing agent (such as modified polyetheramine, triethylenetetramine), an acid anhydride curing agent, or an isocyanate curing agent.

[0030] The microcapsules have an average particle size of 1-100 μm and their wall material is polyurea-formaldehyde resin, polyurethane, urea-formaldehyde resin, melamine resin or a hybrid composite wall material thereof. They contain a repair agent that is released and cured after cracks are generated.

[0031] The repair agent is one or more single-component repair agents selected from drying oils, isocyanate compounds, and cyclic olefin monomers, or a two-component repair system of epoxy resin and curing agent.

[0032] Furthermore, the low-moisture-permeability UV-curable adhesive has a transmittance of not less than 90% in the lanthanum bromide emission band (370-390 nm), a refractive index of 1.52-1.58, a viscosity of 200-2000 mPa·s, and a water vapor transmittance of not more than 5 g / (m²) after curing. 2 • 24h), and the curing shrinkage rate is not higher than 1%;

[0033] The optical window is made of quartz glass, sapphire, borosilicate glass or beryllium, with a thickness of 1-2 mm. Its size is larger than the light-emitting surface size of the lanthanum bromide scintillation crystal body, and the deviation is no more than 0.1 mm.

[0034] This invention also provides a method for preparing a crystal-plane anchored self-healing moisture-resistant reflective encapsulation structure using the above-mentioned lanthanum bromide scintillation crystal, characterized by the following steps:

[0035] 1) In an inert atmosphere glove box with controlled water and oxygen (both water and oxygen content are below 1 ppm), the lanthanum bromide scintillation crystal body is subjected to surface cleaning and low-damage activation treatment; the low-damage activation treatment refers to removing the deliquescent layer and contaminants on the crystal surface by physical grinding or chemical etching, so that the crystal surface is restored to a fresh and clean state, and a micro-rough morphology that is conducive to the subsequent adhesion of the interface layer is formed, and the crystal surface is free from mechanical damage such as deep scratches, microcracks or lattice destruction after treatment.

[0036] 2) On the light-emitting surface of the lanthanum bromide scintillation crystal body, an optical window is bonded with a low moisture permeability UV-curable adhesive and then UV-cured.

[0037] 3) An externally applied nano-anchored moisture-blocking interface layer is formed on the non-light-emitting surface of the lanthanum bromide scintillation crystal body;

[0038] 4) Remove the lanthanum bromide scintillation crystal from the glove box and form a fluoropolymer reflective layer on the outside of the externally added nano-anchored moisture barrier interface layer. Control the process conditions to allow the fluoropolymer melt or powder to flow fully into the surface depression of the mechanical anchoring interface. After solidification, a physical interlocking anchoring structure is formed between the reflective layer and the interface layer, so that the fluoropolymer reflective layer and the externally added nano-anchored moisture barrier interface layer form an interlocking structure.

[0039] 5) A self-healing moisture-proof protective layer is formed on the outside of the fluoropolymer reflective layer to complete the encapsulation of the lanthanum bromide scintillation crystal.

[0040] Further, step 2) specifically involves: uniformly coating a 30-80 μm thick layer of low-moisture-permeable UV-curable adhesive onto the light-emitting surface of the lanthanum bromide scintillation crystal using a needle injection or screen printing method, and then bonding the optical window. Subsequently, a UV-curable adhesive with a strength of 5-20 mW / cm² is applied. 2 Curing is performed by irradiating the product with ultraviolet light for 30-120 seconds.

[0041] Further, in step 3), the specific operation for preparing the externally-added nano-anchored moisture-blocking interface layer is as follows: A low-water-vapor-permeability matrix, inorganic nanoparticles, dispersant I, and curing agent I are mixed uniformly to form a composite slurry, so that the inorganic nanoparticles are uniformly dispersed in the low-water-vapor-permeability matrix; the composite slurry is coated onto the non-light-emitting surface of the lanthanum bromide scintillation crystal body by spraying or dip coating, under conditions of room temperature to 80 °C (preferably 50-70 °C). A continuous coating is formed by curing at ℃. As the solvent evaporates and the coating cures, microphase separation occurs between the low water vapor permeability matrix and the inorganic nanoparticles due to the difference in surface energy. The low water vapor permeability matrix, due to its strong wettability and affinity for the lanthanum bromide scintillation crystal surface, migrates and accumulates towards the lanthanum bromide scintillation crystal body, forming a continuous and dense moisture-blocking phase. Meanwhile, the hydrophobically modified inorganic nanoparticles migrate and accumulate towards the outer surface of the coating under the drive of surface energy. Through the rigid protrusions of the nanoparticles and their aggregation effect, they construct micro-nano-scale uneven morphologies on the outer surface of the coating, thus forming a mechanical anchoring interface. The surface roughness Ra of the side away from the lanthanum bromide scintillation crystal body is .

[0042] The low water vapor permeability matrix has a mass fraction of 70-90 wt% in the composite slurry, preferably 78-88 wt%; the inorganic nanoparticles have a mass fraction of 5-20 wt% in the composite slurry, preferably 8-15 wt%; the dispersant I has a mass fraction of 0.5-5 wt% in the mixed slurry, preferably 1-3 wt%; and the curing agent I has a mass fraction of 0.5-5 wt% in the mixed slurry, preferably 2-4 wt%.

[0043] Further, step 4) specifically involves: removing the lanthanum bromide scintillation crystal from the glove box, depositing a fluoropolymer reflective layer on the outer surface of the externally applied nano-anchored moisture-blocking interface layer using electrostatic spraying technology, then placing the lanthanum bromide scintillation crystal coated with the fluoropolymer reflective layer in an oven, heating it to 140°C at a heating rate of 5°C / min, holding it at that temperature for 10-30 min, and then cooling it to room temperature at a cooling rate of 0.5°C / min.

[0044] Furthermore, in step 5), the specific operation for preparing the self-healing moisture-barrier protective layer is as follows:

[0045] Microcapsules containing the repair agent, dispersant II, and curing agent II are dispersed in a moisture-barrier polymer matrix according to the following mass percentages: microcapsules 1-30 wt%, preferably 5-20 wt%, dispersant 0.1-5 wt%, preferably 0.5-3 wt%, curing agent 0.1-5 wt%, preferably 1-5 wt%, with the remainder being the moisture-barrier polymer matrix. The mixture is stirred at 300-500 rpm for 20-60 minutes to form a uniform slurry. This slurry is then coated onto the outer surface of the fluoropolymer reflective layer using dip coating or spray coating methods and cured at room temperature for 2-48 hours or until the UV intensity reaches 1-10 mW / cm². 2 Irradiate for 5-30 minutes.

[0046] This invention first achieves moisture barrier effect through an externally added nano-anchored moisture-barrier interface layer, allowing the remaining encapsulation to be performed outside the glove box. Then, a fluoropolymer reflective layer optimizes the crystal output performance. Simultaneously, the outermost self-healing moisture-barrier protective layer ensures the stability of the encapsulation. Compared with existing technologies, this invention has the following advantages:

[0047] 1. Significantly reduces the reliance of the packaging process on inert atmosphere glove boxes, making it suitable for mass production.

[0048] In the preparation method of this invention, only the bonding of the light-emitting optical window and the formation of the externally applied nano-anchored moisture-proof interface layer need to be completed inside the glove box. After the above steps have formed a good protective layer on the crystal surface, the subsequent preparation of the fluoropolymer reflective layer and the self-healing moisture-proof protective layer can be removed from the glove box and carried out in a normal environment. By concentrating the critical steps that must be strictly anhydrous and oxygen-free in the front end, the overall process flow is greatly simplified, and the continuous dependence on the large-space, ultra-low water and oxygen content glove box is reduced, making mass production and large-scale production possible.

[0049] 2. Effectively achieves miniaturization and lightweighting of the package.

[0050] This invention employs a low-moisture-permeability UV-curable adhesive to directly bond the optical window to the light-emitting surface, completely eliminating the bulky mechanical assembly structures of traditional solutions, such as metal casings, end caps, and sealing rings. The volume and weight of the package are primarily determined by the crystal and the thin optical window itself, significantly reducing the size compared to traditional metal casing solutions. This meets the urgent needs for lightweight and miniaturized designs in portable detection devices and space-constrained environments. Furthermore, the adhesive layer used possesses both low moisture permeability and low curing shrinkage, ensuring long-term airtightness and stability of the optical interface.

[0051] 3. Enhances the bonding force between the reflective layer and the crystal interface, effectively preventing peeling.

[0052] This invention first constructs an externally applied nano-anchored moisture-blocking interface layer on the surface of a non-light-emitting crystal. This interface layer simultaneously possesses both moisture-blocking and mechanical anchoring functions. The continuous moisture-blocking phase near the crystal effectively prevents water vapor from diffusing and penetrating to the crystal surface; while the side away from the crystal forms a rough mechanical anchoring interface, creating a strong mechanical interlock with the subsequent fluoropolymer reflective layer. This significantly enhances the adhesion of the reflective layer and fundamentally reduces the problem of the reflective layer easily peeling off during temperature cycling, mechanical vibration, or impact.

[0053] 4. Maintain high light collection efficiency to ensure detector performance.

[0054] This invention employs a fluoropolymer reflective layer, achieving a diffuse reflectance exceeding 90% in the main emission band of lanthanum bromide crystals, thus improving scintillation light collection efficiency. Simultaneously, the introduction of a nano-anchoring interface layer does not adversely affect the reflectance. The encapsulated detector effectively maintains excellent light output and energy resolution.

[0055] 5. It endows the packaging layer with self-healing capabilities, extending the service life of the device.

[0056] This invention introduces a self-healing moisture-barrier protective layer on the outermost layer of a multi-layer composite encapsulation structure. This protective layer contains a microencapsulated repair agent. When the encapsulation layer develops microcracks due to mechanical scratches, stress, or aging, the microcapsules rupture, releasing the repair agent, which then solidifies at the crack, autonomously sealing the moisture permeation channels and achieving self-repair of the encapsulation damage. This self-healing moisture-barrier protective layer can achieve a self-repair efficiency of 76% to 93% across different thickness ranges, significantly extending the service life and reliability of the detector under complex operating conditions.

[0057] 6. Achieve multi-functional collaboration and comprehensively improve environmental adaptability.

[0058] This invention constructs a multifunctional collaborative packaging structure of "light-emitting surface window sealing + non-light-emitting surface interface anchoring - high reflection - self-healing moisture barrier". Without increasing the packaging volume and weight, it comprehensively improves the environmental adaptability, light collection efficiency and long-term service reliability of the highly hygroscopic lanthanum bromide scintillation crystal. It is suitable for a variety of application scenarios such as portable nuclear radiation detectors, space-constrained detection modules, unmanned platform radiation monitoring equipment, nuclear safety monitoring equipment and high-performance gamma spectral detectors. Attached Figure Description

[0059] Figure 1 This is a schematic diagram of the layered structure of the lanthanum bromide crystal encapsulation structure of the present invention;

[0060] The attached figures are labeled as follows:

[0061] 1-Lanium bromide scintillation crystal; 2-Externally applied nano-anchored moisture-proof interface layer; 3-Fluoropolymer reflective layer; 4-Self-healing moisture-proof protective layer; 5-Optical window;

[0062] Figure 2 for Figure 1 The flowchart of the packaging structure shown is a fabrication process diagram.

[0063] Figure 3 Reflectance diagrams for polytetrafluoroethylene (PTFE) reflective layer, fluorinated ethylene propylene copolymer reflective layer, and polyvinylidene fluoride (PVDF) reflective layer;

[0064] Figure 4 For testing the gamma response energy spectrum; where a is the gamma response energy spectrum of Example 1 and Example 1 after 7 days of placement; b is the gamma response energy spectrum of Example 2 and Example 2 after 7 days of placement; c is the gamma response energy spectrum of Example 3 and Example 3 after 7 days of placement; d is the gamma response energy spectrum of Example 1 and Example 4 immediately after scratching and Example 4 48 hours after scratching.

[0065] Figure 5 For testing the gamma response energy spectrum; wherein, a is the gamma response energy spectrum tested in Example 1 and Comparative Example 1; b is the gamma response energy spectrum tested in Example 1 and Comparative Example 2; c is the gamma response energy spectrum tested immediately after scratching in Example 1 and Comparative Example 3; d is the gamma response energy spectrum tested 48 hours after scratching in Example 1 and Comparative Example 3; e is the gamma response energy spectrum tested in Example 1 and Comparative Example 4.

[0066] Figure 6Line graphs of light output and energy resolution are shown for fully encapsulated crystals, encapsulated crystals without external nano-anchored moisture-blocking interface layers, encapsulated crystals without fluoropolymer reflective layers, encapsulated crystals with scratched fluoropolymer reflective layers, encapsulated crystals with scratched fluoropolymer reflective layers after 48 hours, and conventionally encapsulated crystals (corresponding to 1, 2, 3, 4, 5, 6 on the horizontal axis, respectively). Among them, a is the light output line graph and b is the energy resolution line graph. Detailed Implementation

[0067] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments:

[0068] Example 1 (Complete encapsulation including an externally added nano-anchored moisture-proof interface layer, a polytetrafluoroethylene reflective layer, and a self-healing moisture-proof protective layer):

[0069] This embodiment provides a packaging structure based on a moisture-barrier interface layer, a polytetrafluoroethylene (PTFE) reflective layer, and a self-healing moisture-barrier protective layer to encapsulate a lanthanum bromide scintillation crystal, with the crystal's light-emitting surface coupled to a quartz glass window.

[0070] Experimental sample:

[0071] LaBr3:Ce scintillation crystal, rectangular in shape, with a square base measuring 6 mm on each side and a height of 30 mm. One of the base surfaces is the light-emitting surface, while the sides and back are non-light-emitting surfaces.

[0072] Packaging steps are as follows Figure 2 As shown, Figure 2 The preparation flow chart shows a process route that can significantly reduce dependence on inert atmosphere and is easier to operate:

[0073] S1. Polish the crystal surface in an inert atmosphere glove box (water and oxygen content <1 ppm) to remove the deliquescent layer, and clean the crystal surface with anhydrous ethanol.

[0074] S2. Bonding the light window: Uniformly coat the light-emitting surface of the crystal with a low moisture permeability UV-curable adhesive (Sekisui Chemicals Photolec). TM Type E, refractive index 1.54, water vapor transmission rate ≤3 g / (m 2 After 24 hours, the quartz glass window (6.1 mm × 6.1 mm, 1 mm thick, with a transmittance of >92% at 370-390 nm) is gently pressed and bonded to remove air bubbles. It is then cured by irradiation with a UV lamp (10 mW / cm²) for 60 seconds, resulting in an adhesive layer thickness of approximately 50 μm.

[0075] S3. Preparation of an externally applied nano-anchored moisture-barrier interface layer: An externally applied nano-anchored moisture-barrier interface layer slurry was sprayed onto the side and back of the crystal. Slurry formulation: hydrophobically modified nano-SiO2 (average particle size 40 nm, mass fraction 12 wt%), anhydrous fluorosilicone resin (balance), dispersant (2 wt%), and curing agent (3 wt%). After spraying, it was cured at 60℃ for 2 hours to form an interface layer with a thickness of approximately 8 μm. The interface layer has a continuous and dense moisture-barrier phase on the side near the crystal, and a rough surface (measured Ra≈1.5 μm) on the side away from the crystal.

[0076] S4. Preparation of polytetrafluoroethylene reflective layer: The crystal is removed from the glove box, and polytetrafluoroethylene micro powder is deposited on the outer surface of the externally attached nano-anchored moisture barrier interface layer using electrostatic spraying technology. The crystal is then placed in an oven and heated to 140°C at a heating rate of 5°C / min. The crystal is then kept at 140°C for 20 minutes for curing. After curing, the crystal is slowly cooled to room temperature at a cooling rate of 0.5°C / min to form a reflective layer with a thickness of 80 μm.

[0077] S5. Preparation of the self-healing moisture-barrier protective layer: Microcapsules containing epoxy repair agent (average particle size 20 μm, mass fraction 12 wt%), epoxy-siloxane hybrid resin matrix (balance), dispersant (2 wt%), and latent curing agent (3 wt%) are mixed evenly. The mixture is then dip-coated onto the outer surface of the reflective layer, with a controlled thickness of 100 μm. Curing is performed at room temperature for 24 hours to form a self-healing moisture-barrier protective layer, completing the encapsulation process. The structure is as follows: Figure 1 As shown, Figure 1 The multi-layer composite encapsulation structure of the present invention is shown (from the inside out, it consists of an externally added nano-anchored moisture barrier interface layer 2, a fluoropolymer reflective layer 3, and a self-healing moisture barrier protective layer 4).

[0078] test:

[0079] Place the package in a room temperature atmospheric environment and use 137 The gamma spectrum was measured using a Cs radioactive source (662 keV) for 900 s, with a gain of 25, a voltage of 800 V, and a shaping time of 0.5 μs. The light output peak position and energy resolution were recorded. After the package was placed in a room temperature atmospheric environment for 7 days, its energy spectrum was measured again under the same test conditions.

[0080] The results are as follows Figure 4 a and Figure 6 As shown:

[0081] The light output peak was at channel 1262 with an energy resolution of 3.3%. Seven days later, the light output peak was at channel 1230 with an energy resolution of 3.31%.

[0082] Example 2 (Complete encapsulation including an externally added nano-anchored moisture-proof interface layer, a fluorinated ethylene propylene copolymer reflective layer, and a self-healing moisture-proof protective layer)

[0083] This embodiment provides a packaging structure based on a moisture-barrier interface layer, a fluorinated ethylene propylene copolymer (FEP) reflective layer, and a self-healing moisture-barrier protective layer encapsulating a lanthanum bromide scintillation crystal, with the crystal's light-emitting surface coupled to a quartz glass window.

[0084] Experimental sample:

[0085] LaBr3:Ce scintillation crystal, rectangular in shape, with a square base measuring 6 mm on each side and a height of 30 mm. One of the base surfaces is the light-emitting surface, while the sides and back are non-light-emitting surfaces.

[0086] Packaging steps:

[0087] S1. Polish the crystal surface in an inert atmosphere glove box (water and oxygen content <1 ppm) to remove the deliquescent layer, and clean the crystal surface with anhydrous ethanol.

[0088] S2. Bonding the light window: Uniformly coat the light-emitting surface of the crystal with a low moisture permeability UV-curable adhesive (Sekisui Chemicals Photolec). TM Type E, refractive index 1.54, water vapor transmission rate ≤3 g / (m 2 After 24 hours, the quartz glass window (6.1 mm × 6.1 mm, 1 mm thick, with a transmittance of >92% at 370-390 nm) is gently pressed and bonded to remove air bubbles. It is then cured by irradiation with a UV lamp (10 mW / cm²) for 60 seconds, resulting in an adhesive layer thickness of approximately 50 μm.

[0089] S3. Preparation of an externally applied nano-anchored moisture-barrier interface layer: An externally applied nano-anchored moisture-barrier interface layer slurry was sprayed onto the side and back of the crystal. Slurry formulation: hydrophobically modified nano-SiO2 (average particle size 40 nm, mass fraction 12 wt%), anhydrous fluorosilicone resin (balance), dispersant (2 wt%), and curing agent (3 wt%). After spraying, it was cured at 60℃ for 2 hours to form an interface layer with a thickness of approximately 8 μm. The interface layer has a continuous and dense moisture-barrier phase on the side near the crystal, and a rough surface (measured Ra≈1.5 μm) on the side away from the crystal.

[0090] S4. Preparation of fluorinated ethylene propylene copolymer reflective layer: The crystal is removed from the glove box, and fluorinated ethylene propylene copolymer micropowder is deposited on the outer surface of the externally applied nano-anchored moisture barrier interface layer using electrostatic spraying technology. The crystal is then placed in an oven and heated to 180°C at a heating rate of 5°C / min. The crystal is then kept at 180°C for 20 minutes to allow the FEP micropowder to fully melt and flow into the surface depressions of the mechanical anchoring interface. After curing, the crystal is slowly cooled to room temperature at a cooling rate of 0.5°C / min to form a reflective layer with a thickness of 100 μm. This reflective layer forms an intercalation structure with the externally applied nano-anchored moisture barrier interface layer.

[0091] S5. Preparation of the self-healing moisture-barrier protective layer: Microcapsules containing epoxy repair agent (average particle size 20 μm, mass fraction 12 wt%), epoxy-siloxane hybrid resin matrix (balance), dispersant (2 wt%), and latent curing agent (3 wt%) are mixed evenly. The mixture is then dip-coated onto the outer surface of the reflective layer, with a thickness controlled at 100 μm. It is cured at room temperature for 24 hours to form a self-healing moisture-barrier protective layer, completing the encapsulation process.

[0092] test:

[0093] Place the package in a room temperature atmospheric environment and use 137 The gamma spectrum was measured using a Cs radioactive source (662 keV) for 900 s, with a gain of 25, a voltage of 800 V, and a shaping time of 0.5 μs. The light output peak position and energy resolution were recorded. After the package was placed in a room temperature atmospheric environment for 7 days, its energy spectrum was measured again under the same test conditions.

[0094] The results are as follows Figure 4 As shown in b:

[0095] The light output peak was at channel 1231 with an energy resolution of 3.35%. Seven days later, the light output peak was at channel 1208 with an energy resolution of 3.36%.

[0096] Example 3 (Complete encapsulation including an externally added nano-anchored moisture-proof interface layer, a polyvinylidene fluoride reflective layer, and a self-healing moisture-proof protective layer)

[0097] This embodiment provides a packaging structure based on a moisture-barrier interface layer, a polyvinylidene fluoride (PVDF) reflective layer, and a self-healing moisture-barrier protective layer to encapsulate a lanthanum bromide scintillation crystal, with the crystal's light-emitting surface coupled to a quartz glass window.

[0098] Experimental sample:

[0099] LaBr3:Ce scintillation crystal, rectangular in shape, with a square base measuring 6 mm on each side and a height of 30 mm. One of the base surfaces is the light-emitting surface, while the sides and back are non-light-emitting surfaces.

[0100] Packaging steps:

[0101] S1. Polish the crystal surface in an inert atmosphere glove box (water and oxygen content <1 ppm) to remove the deliquescent layer, and clean the crystal surface with anhydrous ethanol.

[0102] S2. Bonding the light window: Uniformly coat the light-emitting surface of the crystal with a low moisture permeability UV-curable adhesive (Sekisui Chemicals Photolec). TM Type E, refractive index 1.54, water vapor transmission rate ≤3 g / (m 2 (24h) Then, gently press and adhere the quartz glass window (6.1 mm × 6.1 mm, 1 mm thick, transmittance >92% at 370-390 nm) to remove air bubbles. Use a UV lamp (10 mW / cm²) 2 After irradiation for 60 seconds, the adhesive layer will cure and be approximately 50 μm thick.

[0103] S3. Preparation of an externally applied nano-anchored moisture-barrier interface layer: An externally applied nano-anchored moisture-barrier interface layer slurry was sprayed onto the side and back of the crystal. Slurry formulation: hydrophobically modified nano-SiO2 (average particle size 40 nm, mass fraction 12 wt%), anhydrous fluorosilicone resin (balance), dispersant (2 wt%), and curing agent (3 wt%). After spraying, it was cured at 60℃ for 2 hours to form an interface layer with a thickness of approximately 8 μm. The interface layer has a continuous moisture-barrier phase on the side near the crystal and a rough surface (measured Ra≈1.5 μm) on the side away from the crystal.

[0104] S4. Prepare a polyvinylidene fluoride (PVDF) reflective layer. Remove the crystal from the glove box and uniformly coat the PVDF solution onto the outer surface of the externally applied nano-anchored moisture-blocking interface layer using a spraying method. Place the layer in an oven and heat it to 160°C at a heating rate of 5°C / min. Keep it at 160°C for 30 minutes to cure the PVDF coating fully and allow it to flow into the surface depressions of the mechanical anchoring interface. After curing, slowly cool it to room temperature at a cooling rate of 0.5°C / min to form a reflective layer with a thickness of 90 μm. This reflective layer forms an intercalation structure with the externally applied nano-anchored moisture-blocking interface layer.

[0105] S5. Preparation of a self-healing moisture-barrier protective layer: Microcapsules containing epoxy repair agent (average particle size 20 μm, mass fraction 12 wt%), epoxy-siloxane hybrid resin matrix (balance), dispersant (2 wt%), and latent curing agent (3 wt%) are mixed evenly. The mixture is then dip-coated onto the outer surface of the reflective layer, with a controlled thickness of 100 μm. It is cured at room temperature for 24 hours to form a self-healing moisture-barrier protective layer, which is then completely encapsulated.

[0106] test:

[0107] Place the package in a room temperature atmospheric environment and use 137The gamma spectrum was measured using a Cs radioactive source (662 keV) for 900 s, with a gain of 25, a voltage of 800 V, and a shaping time of 0.5 μs. The light output peak position and energy resolution were recorded. After the package was placed in a room temperature atmospheric environment for 7 days, its energy spectrum was measured again under the same test conditions.

[0108] The results are as follows Figure 4 As shown in c:

[0109] The light output peak was at channel 1214 with an energy resolution of 3.38%. Seven days later, the light output peak was at channel 1200 with an energy resolution of 3.39%.

[0110] Meanwhile, the present invention also tested the reflectivity of the three reflective layers used in Examples 1-3. As can be seen from the figure, the polytetrafluoroethylene reflective layer has the highest reflectivity.

[0111] Example 4 (Complete encapsulation including an externally added nano-anchored moisture-proof interface layer, a polytetrafluoroethylene reflective layer, and a self-healing moisture-proof protective layer, with a scratched surface)

[0112] Experimental sample:

[0113] LaBr3:Ce scintillation crystal, rectangular in shape, with a square base measuring 6 mm on each side and a height of 30 mm. One of the base surfaces is the light-emitting surface, while the sides and back are non-light-emitting surfaces.

[0114] Packaging steps:

[0115] The difference from Example 1 is that it also includes:

[0116] S6. Artificial scratching of the surface: A penetrating scratch approximately 100 μm wide and 10 mm long is made on the surface of the self-healing moisture-proof protective layer and the fluoropolymer reflective layer (done in a dry atmosphere), with the scratch depth penetrating the self-healing protective layer and extending into the interior of the reflective layer.

[0117] test:

[0118] Place the scratched package in a room temperature atmospheric environment and use... 137 The gamma spectrum was measured using a Cs radioactive source (662 keV) for 900 s, with a gain of 25, a voltage of 800 V, and a shaping time of 0.5 μs. The peak position and energy resolution of the light output were recorded immediately after the scratch and 48 hours after the scratch, and compared with the results of Example 1 (complete packaging without scratches).

[0119] The results are as follows Figure 4 As shown in d:

[0120] Immediately after the scratch, the light output peak was 1129 channels, and the energy resolution was 3.6%, decreasing to 89.4% of the complete package in Example 1 (1262 channels, 3.3%). After the scratched package was placed in a room temperature atmospheric environment for 48 hours and tested again, the light output peak recovered to 1235 channels, and the energy resolution was 3.31%, with the light output recovering to 97.9% of the complete package in Example 1. The energy resolution was basically restored to the level before the scratch, thus demonstrating that the packaging structure of the present invention has a strong self-healing capability.

[0121] Depend on Figure 4 As can be seen, Examples 1 (PTFE reflective layer), 2 (FEP reflective layer), and 3 (PVDF reflective layer) using the complete three-layer composite encapsulation structure of this invention all exhibited clear photoelectric peaks in their gamma-ray spectra during initial testing in a room-temperature atmospheric environment. The light output peak positions were 1262, 1231, and 1214, respectively, with energy resolutions of 3.3%, 3.35%, and 3.38%. After placing the encapsulation in a room-temperature atmospheric environment for 7 days, the light output peak positions for each example were 1230 (Example 1), 1208 (Example 2), and 1200 (Example 3), respectively, with energy resolutions of 3.31%, 3.36%, and 3.39%, and light output retention rates all exceeding 97%. After scratching, with the completion of the repair process, the moisture penetration path was effectively blocked, and the structural integrity of the reflective layer was restored to a certain extent, thereby restoring the light output of the encapsulation from 1129 channels after the scratch to 1235 channels, a recovery rate of 91.4%. This indicates that the outermost self-healing moisture-proof protective layer of the present invention endows the packaging structure with effective damage self-healing capability, significantly extending the service life and reliability of the package under complex service conditions.

[0122] Comparative Example 1 (without an externally added nano-anchored moisture-proof interface layer)

[0123] This comparative example is used to verify the rapid deliquescence behavior of the crystal under non-resistance moisture packaging.

[0124] Experimental sample: LaBr3:Ce crystals from the same batch as in Example 1, with the same size.

[0125] Packaging steps:

[0126] S1. Perform surface cleaning and bonding of the light-emitting window as in Example 1.

[0127] S2. Omit the external nano-anchoring moisture barrier interface layer: Do not coat any external nano-anchoring moisture barrier slurry on the non-light-emitting surface of the crystal, and proceed directly to the next step.

[0128] S3. Wrap a polytetrafluoroethylene reflective layer (120 μm thick, cured at 140°C) as in Example 1.

[0129] S4. Prepare a self-healing moisture-proof protective layer (100 μm thick, room temperature curing) in the same manner as in Example 1.

[0130] test:

[0131] The crystal was placed in a room temperature atmospheric environment for 7 days, and the changes in its surface appearance were recorded with a camera every 12 hours. 137 Cs radiation source (662 keV) test light output (using temporary coupling method).

[0132] The comparison results with Example 1 are as follows: Figure 5 a and Figure 6 As shown:

[0133] After the package was placed in a room temperature atmospheric environment for 7 days, disassembly revealed obvious white deliquescence spots on the side of the crystal, the light output dropped to 50.2% of the initial value (633 channels vs 1262 channels), and the energy resolution deteriorated to 4.1%.

[0134] Comparative Example 2 (without fluoropolymer reflective layer)

[0135] This comparative example is used to verify the contribution of the reflective layer to the light collection efficiency.

[0136] Experimental sample: LaBr3:Ce crystals from the same batch as in Example 1, with the same size.

[0137] Packaging steps:

[0138] S1. Perform surface cleaning and bonding of the light-emitting window as in Example 1.

[0139] S2. Prepare an externally attached nano-anchored moisture-blocking interface layer (8 μm thick, cured at 60°C) as in Example 1.

[0140] S3. Omit the fluoropolymer reflective layer: Do not wrap any reflective material.

[0141] S4. Prepare a self-healing moisture-proof protective layer (100 μm thick, room temperature curing) in the same manner as in Example 1.

[0142] test:

[0143] Under the same test conditions ( 137 (Cs radiation source), recording the light output peak position and energy resolution of the package.

[0144] The comparison results with Example 1 are as follows: Figure 5 b and Figure 6 As shown:

[0145] The initial light output was only 20.4% of that of Example 1 (257 channels vs 1262 channels), and the energy resolution deteriorated to 9.7%. This was due to a large amount of scintillation light leaking from the side without the reflective layer, indicating that the fluoropolymer reflective layer can improve the light collection efficiency by about 79.6%.

[0146] Comparative Example 3 (without a self-healing moisture-proof protective layer, and intentionally scratched on the fluoropolymer reflective layer)

[0147] This comparative example is used to simulate the impact of damage to the fluoropolymer reflective layer on light collection performance, to illustrate the importance of maintaining the integrity of the reflective layer.

[0148] Experimental sample: LaBr3:Ce crystals from the same batch as in Example 1, with the same size.

[0149] Packaging steps:

[0150] S1. Perform the same surface cleaning, light-emitting window bonding, coating of external nano-anchoring moisture-proof interface layer, and wrapping of fluoropolymer reflective layer (120 μm thick, cured at 140°C) as in Example 1.

[0151] S2. Omit the self-healing moisture barrier layer: Do not apply the self-healing moisture barrier layer.

[0152] S3. Intentionally scratching the fluoropolymer reflective layer: Make a scratch about 100 μm wide and 10 mm long on the surface of the fluoropolymer reflective layer (in a dry atmosphere).

[0153] test:

[0154] Under the same test conditions ( 137 (Cs radioactive source), recording the light output peak position and energy resolution of the package.

[0155] The comparison results with Example 1 are as follows: Figure 5 c, d and Figure 6 As shown:

[0156] Immediately after the scratch was tested, the light output dropped to 79.9% of that in Example 1 (1008 channels vs. 1262 channels), and the energy resolution deteriorated to 3.6%. After placing the package in a dry atmosphere at room temperature for 48 hours, the light output continued to decrease (to 63.8% of the initial value (805 channels vs. 1262 channels)), and the energy resolution deteriorated to 3.8%. This indicates that without a self-healing layer, the moisture channels caused by the scratch cannot be sealed, and the package structure fails rapidly.

[0157] Comparative Example 4 (Existing technology packaging - metal shell + PTFE reflective layer, no anchoring interface, no self-healing layer)

[0158] This comparative example uses a typical metal casing packaging scheme in the prior art and compares it with Embodiment 1 of the present invention to demonstrate the advantages of the present invention in terms of light output retention rate and volume and weight.

[0159] Experimental sample: LaBr3:Ce crystals from the same batch as in Example 1, with the same size.

[0160] Packaging steps:

[0161] S1. The crystal surface is cleaned in the same way as in Example 1 in the glove box.

[0162] S2. Bonding the quartz glass window sheet to the light-emitting surface: Same as in Example 1, using the same low moisture permeability UV-curing adhesive (Sekisui Chemicals Photolec). TM (Type E), with the same curing conditions.

[0163] S3. Reflective layer wrapping: Two layers of polytetrafluoroethylene raw material tape (total thickness of about 200 μm) are tightly wrapped around the side and back of the crystal and fixed with polytetrafluoroethylene tape. There is no external nano-anchoring moisture barrier interface layer.

[0164] S4. Metal housing encapsulation: The encapsulated crystal is placed into an aluminum alloy housing (wall thickness 2 mm, inner diameter 10 mm, height 33 mm, with a sealing cap and a 1 mm rear optical window at the bottom).

[0165] test:

[0166] Under the same test conditions ( 137 (Cs radioactive source), recording the light output peak position and energy resolution of the package.

[0167] The results are as follows Figure 5 e and Figure 6 As shown: the light output peak is at channel 1180, and the energy resolution is 3.32%.

[0168] Figure 5 and Figure 6 It can be seen that, after 7 days, the light output of Comparative Example 1 (without the external nano-anchored moisture-blocking interface layer) was only 633 channels, which decreased to 50.2% of the initial value, and the energy resolution deteriorated to 4.1%, verifying the key moisture-blocking role of the external nano-anchored moisture-blocking interface layer. Figure 5 a, Figure 6 Position 1 vs 2). Comparative Example 2 (without fluoropolymer reflective layer) had only 257 light output channels, which is 20.4% of Example 1, and the energy resolution deteriorated to 9.7%, demonstrating that the fluoropolymer reflective layer can improve light collection efficiency by approximately 79.6%. Figure 5 b, Figure 6Position 1 vs 3). In Comparative Example 3 (without self-healing moisture-proof protective layer), the light output after scratching decreased from 1008 channels to 805 channels after 48 hours, and the energy resolution deteriorated from 3.6% to 3.8%, indicating that the moisture channels could not be sealed without the self-healing layer; while in Example 1, the outermost microcapsule ruptured to release the repair agent and seal the crack, thus maintaining long-term stability (Figures 5c-d). Figure 6 Position 1 vs 4, 5). Comparative Example 4 (metal casing + PTFE) has an optical output of 1180 channels. Figure 5 The number of layers (e) is lower than that of Example 1 (1262), and the outer shell wall thickness is 2 mm, resulting in a package volume and weight that are much larger than the multilayer thin film package structure of the present invention.

[0169] In summary, this invention improves the environmental stability, light collection efficiency, and long-term service reliability of the highly hygroscopic lanthanum bromide scintillation crystal package through the synergistic effect of interface anchoring, light reflection, and self-healing moisture barrier.

[0170] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the scope of the technology disclosed in the present invention, and such modifications or substitutions should all be covered within the scope of protection of the present invention.

Claims

1. A crystal plane anchoring type self-healing moisture-proof and reflective encapsulation structure for a lanthanum bromide scintillation crystal, characterized in that: This includes a composite layer and an optical window that work together to encapsulate the lanthanum bromide scintillation crystal body; The composite layer is used to encapsulate the non-light-emitting surface of the lanthanum bromide scintillation crystal body, and from the inside out, it includes an externally added nano-anchored moisture-proof interface layer, a fluoropolymer reflective layer, and a self-healing moisture-proof protective layer. The optical window is used to encapsulate the light-emitting surface of the lanthanum bromide scintillation crystal body and the end face of the composite layer flush with the light-emitting surface. It is bonded to the light-emitting surface and the end face of the composite layer by a low moisture permeability UV curing adhesive.

2. The crystal plane anchoring self-healing moisture-resistant and reflective encapsulation structure of the lanthanum bromide scintillation crystal according to claim 1, characterized in that: The externally added nano-anchored moisture-blocking interface layer has a continuous and dense moisture-blocking phase on the side close to the lanthanum bromide scintillation crystal body, and a mechanical anchoring interface with an uneven morphology on the side away from the lanthanum bromide scintillation crystal body, with a thickness of 8-10 μm, wherein the surface roughness Ra of the mechanical anchoring interface is 1.3-2.3 μm. The externally added nano-anchored moisture-proof interface layer is prepared from a low water vapor permeability matrix, inorganic nanoparticles, dispersant I, and curing agent I; The low water vapor permeability matrix is ​​one or more of fluorosilicone resin, fluorocarbon resin, modified organosilicon resin, or parylene. The inorganic nanoparticles are one or more of hydrophobically modified nano-silica, nano-alumina, or nano-titanium dioxide, with an average particle size of 10-100 nm. The dispersant I is one or more of the following: polymeric dispersant, siloxane dispersant, wetting dispersant, and phosphate ester dispersant; The curing agent I is one or more of the following: isocyanate curing agents, amine curing agents, acid anhydride curing agents, and latent curing agents.

3. The crystal plane anchoring self-healing moisture-resistant and reflective encapsulation structure of the lanthanum bromide scintillation crystal according to claim 2, characterized in that: The fluoropolymer reflective layer is a polytetrafluoroethylene micro powder layer, expanded polytetrafluoroethylene film, polytetrafluoroethylene composite coating, fluorinated ethylene propylene copolymer coating, or polyvinylidene fluoride coating. It forms an interlocking structure with the mechanical anchoring interface, has a thickness of 80-120 μm, and has a reflectivity greater than 90% in the lanthanum bromide emission band of 370-390 nm.

4. The crystal plane anchoring self-healing moisture-resistant and reflective encapsulation structure of the lanthanum bromide scintillation crystal according to claim 3, characterized in that: The thickness of the self-healing moisture-proof protective layer is 5-500 μm, and it is prepared from a moisture-proof polymer matrix, microcapsules, dispersant II and curing agent II; The moisture-barrier polymer matrix is ​​epoxy resin, polyurethane resin, silicone resin, fluorocarbon resin or acrylic resin; The dispersant II is polyethylene glycol, polyvinyl alcohol, sodium polyacrylate, phosphate ester dispersant, or polymer block copolymer dispersant; The curing agent II is a latent curing agent, an amine curing agent, an acid anhydride curing agent, or an isocyanate curing agent; The microcapsules have an average particle size of 1-100 μm, and their wall material is polyurea-formaldehyde resin, polyurethane, urea-formaldehyde resin, melamine resin or a hybrid composite wall material thereof, and they are encapsulated with a repair agent. The repair agent is one or more single-component repair agents selected from drying oils, isocyanate compounds, and cyclic olefin monomers, or a two-component repair system of epoxy resin and curing agent.

5. The crystal plane anchoring self-healing moisture-resistant reflective encapsulation structure of the lanthanum bromide scintillation crystal according to any one of claims 1-4, characterized in that: The low-moisture-permeability UV-curable adhesive has a transmittance of no less than 90% in the lanthanum bromide emission band (370-390 nm), a refractive index of 1.52-1.58, a viscosity of 200-2000 mPa·s, and a water vapor transmittance of no more than 5 g / (m²) after curing. 2 • 24h), and the curing shrinkage rate is not higher than 1%; The optical window is made of quartz glass, sapphire, borosilicate glass or beryllium, with a thickness of 1-2 mm. Its size is larger than the light-emitting surface size of the lanthanum bromide scintillation crystal body, and the deviation is no more than 0.1 mm.

6. A method for preparing a crystal plane anchored self-healing moisture-resistant reflective encapsulation structure of the lanthanum bromide scintillation crystal according to any one of claims 1-5, characterized in that, Includes the following steps: 1) The lanthanum bromide scintillation crystal body was subjected to surface cleaning and low-damage activation treatment in an inert atmosphere glove box with both water and oxygen content below 1 ppm. 2) On the light-emitting surface of the lanthanum bromide scintillation crystal body, a low-moisture-permeable UV-curable adhesive is uniformly coated and bonded to the optical window, and then UV-cured. 3) An externally applied nano-anchored moisture-blocking interface layer is formed on the non-light-emitting surface of the lanthanum bromide scintillation crystal body; 4) Remove the lanthanum bromide scintillation crystal from the glove box and form a fluoropolymer reflective layer on the outside of the externally added nano-anchored moisture barrier interface layer, so that the fluoropolymer reflective layer and the externally added nano-anchored moisture barrier interface layer form an interlocking structure. 5) A self-healing moisture-proof protective layer is formed on the outside of the fluoropolymer reflective layer to complete the encapsulation of the lanthanum bromide scintillation crystal.

7. The preparation method according to claim 6, characterized in that, Step 2) specifically involves: A low-moisture-permeability UV-curable adhesive with a thickness of 30-80 μm was uniformly coated onto the light-emitting surface of the lanthanum bromide scintillation crystal using needle injection or screen printing dispensing methods. The optical window was then bonded, followed by application of a UV-curable adhesive with a strength of 5-20 mW / cm². 2 Curing is performed by irradiating the product with ultraviolet light for 30-120 seconds.

8. The preparation method according to claim 7, characterized in that: In step 3), the specific operation for preparing the externally-added nano-anchored moisture-blocking interface layer is as follows: a low water vapor transmission rate substrate, inorganic nanoparticles, dispersant I and curing agent I are mixed evenly to form a composite slurry, so that the inorganic nanoparticles are uniformly dispersed in the low water vapor transmission rate substrate; the composite slurry is coated onto the non-light-emitting surface of the lanthanum bromide scintillation crystal body by spraying or dip coating, and cured at room temperature to 80 ℃ to form a continuous coating. The low water vapor permeability matrix has a mass fraction of 70-90 wt% in the composite slurry; the inorganic nanoparticles have a mass fraction of 5-20 wt% in the composite slurry; the dispersant I has a mass fraction of 0.5-5 wt% in the mixed slurry; and the curing agent I has a mass fraction of 0.5-5 wt% in the mixed slurry.

9. The preparation method according to claim 8, characterized in that, Step 4) specifically involves: The lanthanum bromide scintillation crystal was removed from the glove box, and a fluoropolymer reflective layer was deposited on the outer surface of the externally applied nano-anchored moisture-blocking interface layer using electrostatic spraying technology. Then, the lanthanum bromide scintillation crystal with the fluoropolymer reflective layer was placed in an oven and heated to 140°C at a heating rate of 5°C / min. After curing at this temperature for 10-30 min, it was cooled to room temperature at a cooling rate of 0.5°C / min.

10. The preparation method according to claim 9, characterized in that: In step 5), the specific steps for preparing the self-healing moisture-barrier protective layer are as follows: Microcapsules containing the repair agent, dispersant II, and curing agent II are dispersed in the moisture-barrier polymer matrix according to the following mass percentages: microcapsules 1-30 wt%, dispersant 0.1-5 wt%, curing agent 0.1-5 wt%, with the balance being the moisture-barrier polymer matrix. The mixture is stirred at 300-500 rpm for 20-60 min to form a homogeneous slurry. This slurry is then coated onto the outer surface of the fluoropolymer reflective layer using dip coating or spray coating methods. Curing is performed at room temperature for 2-48 h or until the UV intensity reaches 1-10 mW / cm². 2 Irradiate for 5-30 minutes.

Citation Information

Patent Citations

  • Waterless encapsulated scintillation crystal assembly, encapsulation method and detector

    CN107390251B

  • Scintillation crystal packaging methods, scintillation crystal packaging structures and their applications

    CN109459782B

  • Logging high-temperature-resistant packaged lanthanum bromide crystal and packaging method thereof

    CN110592669A

  • Packaging film for deliquescent scintillation crystal

    CN215728863U